Contesting the hub-and-spokes model in Southeast Asia - Willoughby, Charmaine Misalucha- (Animo Repository, 2020)
The debate surrounding the United States’ hub-and-spokes alliance model in the Asia-Pacific, that is, whether its endurance is a testament to its durability or whether its inability to face up to contemporary challenges reflects its failure—is best captured by recent norm research in International Relations. It can be argued that the U.S. hub-and-spokes model in Southeast Asia is not failing but is simply showing signs of contestation. The evolution of this network of regional security arrangements from U.S. alliances in Southeast Asia (with the Philippines and Thailand) to American security partnerships in that subregion (strategic partnership with Singapore and comprehensive partnership with Vietnam) reflects applicatory contestation. At the same time, the China factor and Washington’s evolving Asia strategy, which competes with the Middle East and with the “America First” instincts of the Trump administration, challenge the core of the San Francisco System’s validity. Hence, while the hub-and-spokes model is merely showing signs of contestation, the fact that it is undergoing validity contestation serves as a cautionary tale. Those U.S. policymakers supporting it will need to implement steps to avoid its complete erosion. © 2019 Policy Studies Organization